A Review of Enterotoxigenic Escherichia coli Infection in Piglets: Public Health Importance - Erwan Budi Hartad, - (Medknow Publications, 2020)
Diarrhea in piglets can cause health problems and even death. The cause is often infection by enterotoxigenic Escherichia coli (ETEC). This condition can have an impact on the growth of pigs and the economy of farmers, the cause can also be transmitted to humans which has an impact on public health. Diarrhea is one of the main health problems of piglets, because it attacks the digestive tract, especially the intestines. The main virulence factors are adhesin (fimbriae) and enterotoxins, with the most frequently found being ETEC F4 (K88) and F18. Fimbriae F4 (K88) ETEC causes diarrhea in neonatal pigs, while fimbriae F18 causes diarrhea in post-weaning pigs (PWD). Meanwhile, enterotoxin is divided into two types, namely heat labile enterotoxin (LT) and heat resistant enterotoxin (ST). After attaching it to the intestinal mucosa, E. coli will colonize and produce enterotoxins. Neonatal diarrhea is usually observed in piglets 1-4 days of age, while post-weaning diarrhea occurs in piglets 2-3 weeks after weaning with a peak diarrhea occurring 6-8 weeks post weaning, and even at 12 weeks. The large amount of water and electrolyte secretions causes dehydration, metabolic acidosis, osmotic diarrhea and a high probability of death before 2 weeks. Currently, there are many incidents of antibiotic resistance, so an alternative use of antibiotics is needed in pig farms to prevent ETEC infection. Alternative antibiotics that can be used to prevent infection with ETEC infection in piglets are immunoprophylaxis, antimicrobial minerals (such as zinci oxide and cupri sulfate), acidifiers, blood plasma, egg yolk antibodies, probiotics, nucleotides, bacteriophages and so on. These kinds of alternatives and feed additives can improve intestinal health and prevent diarrhea in piglets. This review contains the latest research from various journals discussing how ETEC can infect piglets and the management against the disease